Discursive resistance to gender diversity in sport governance: sport as a unique field?. Issue 3 (3rd July 2021) - Knoppers, Annelies; Spaaij, Ramon; Claringbould, Inge
ABSTRACT: Although diversity is an often cited organisational value, its support is often muted when it pertains to boards of governance. The aim of this study is to identify discursive practices that may prevent or limit the implementation of measures to increase gender balance in sport governance at the national and international levels. Drawing on a total of 60 qualitative, semi-structured interviews with board members, we explore both the content of and reasons for discursive opposition to implementing gender balance in the governing boards of international and national sport organisations that purport to value diversity. The results demonstrate that board members justify their resistance to gender balance by drawing on discourses of meritocracy, neoliberalism, silence/passivity, and diversity. Resistance to gender balance in sport governance may in part have roots in the sport capital and habitus of board members, and their ability to utilise that in normalising judgment that may keep women out.